Erkölcsi és emberi méltóság a középkori keresztény filozófiában - Barcsi, Tamás (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
In my study, I will interpret the concepts of moral dignity and human dignity in medieval and Renaissance ethics and philosophy of law, without aiming to be exhaustive. First, I will discuss the various meanings of dignity and refer to Cicero's ideas, which are of fundamental importance for our topic. I will then discuss the Christian understanding of dignity, draw attention to some of the relevant views of St Augustine and St Thomas Aquinas, discuss Dante Alighieri's concept of nobility, and review Pico della Mirandola's seminal understanding of dignity. I will conclude by exploring the interrelations between the conceptions examined.